Antisense oligonucleotides for the arterial hypertension mechanisms study and therapy - L. O. Klimov; A. A. Seryapina; V. F. Zarytova; A. S. Levina; A. L. Markel (Вавиловский журнал генетики и селекции)
Arterial hypertension is one of the most common chronic diseases in adults all over the world. This pathology can not only reduce patients’ life quality, but can also be accompanied by a number of complications. Despite the fact that there is a large group of antihypertensive drugs on the market, mainly representing different combinations of inhibitors of the renin-angiotensin system, adrenoreceptor blockers in combination with diuretics, there is no generally accepted “gold standard” for drugs that would not have side effects. The review discusses the main aspects of antisense oligonucleotides use in the context of arterial hypertension. It is well known that the medical implementation of antisense oligonucleotides aims to block the expression of particular genes involved in the pathology development, and a key advantage of this technique is a high selectivity of the effect. However, with the undoubted advantages of the method, there are difficulties in its application, related both to the properties of the oligonucleotides themselves (insufficient stability and poor penetration into cells), and to the variety of mechanisms of the origin of a particular pathology, arterial hypertension, in our case. The review provides a brief description of the main molecular targets for antisense treatment of hypertensive disease. The newest targets for therapy with oligonucleotides – microRNAs – are discussed. The main modifications of antisense nucleotides, designed to increase the duration of their effects and simplify the delivery of this type of drugs to the targets are discussed, in particular, combining antisense oligonucleotides with adenovirus-based expression vectors. Particular attention is given to antisense oligonucleotides in the complex with nanoparticles. The review discusses the results of the use of titanium dioxide (TiO2) containing antisense nanocomposites for the angiotensin converting enzyme in rats with stress induced arterial hypertension (ISIAH). It was shown that the use of antisense oligonucleotides continues to be a promising technique for studying the mechanisms of various forms of hypertensive disease and has a high potential for therapeutic use.